2011
DOI: 10.2169/internalmedicine.50.4600
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Smoking Cessation and Weight Gain on Plasma Adiponectin Levels and Insulin Resistance

Abstract: Background Tobacco smoking is a major risk factor for atherosclerotic and cardiovascular disease. Studies have found evidence that smoking cessation is associated with weight gain, which is itself a leading cause of cardiovascular disease. Aim The present study sought to determine how smoking cessation and associated weight gain affect adiponectin levels and insulin resistance. Methods Fifty-two male habitual smokers were treated for 2 months with transdermal nicotine patches, and the 28 subjects who successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
17
1
1
Order By: Relevance
“…However, no significant changes in adiponectin levels or HOMA index were found in the weight-maintaining group. Overall, the results of this study showed that post-cessation weight gain is associated with decreased adiponectin levels and increased risk of the metabolic syndrome 91 .…”
Section: Smoking Cessationmentioning
confidence: 55%
See 1 more Smart Citation
“…However, no significant changes in adiponectin levels or HOMA index were found in the weight-maintaining group. Overall, the results of this study showed that post-cessation weight gain is associated with decreased adiponectin levels and increased risk of the metabolic syndrome 91 .…”
Section: Smoking Cessationmentioning
confidence: 55%
“…An inverse association exists between levels of adiponectin and an increased risk of developing the metabolic syndrome 90 . In a study of 28 male smokers who successfully abstained from smoking for 2 months with the aid of transdermal nicotine treatment, individuals were divided into two groups: weight maintainers ( n = 10) and weight gainers ( n = 18) 91 . In the weight-gaining group, serum levels of adiponectin increased 1 week after initiation of transdermal nicotine therapy; at 9 weeks, levels of adiponectin were markedly decreased.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Interestingly, we also found that there was higher prevalence of ex-smokers than current smokers in the co-PreHTN and PreDM group. This observation can be explained by the findings of Inoue K [21], who suggested that the adverse effects associated with the weight gain following cessation of smoking outweigh the benefits. Weight gain is a strong risk factor for CVD, which is also closely associated with a substantial risk for impaired glucose regulation and elevated BP [22].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a difference in apolipoprotein A1 and B and cystatin C with ethnicity indicates that adiponectin holds the greatest promise as a biomarker of cardiovascular risk post-transplantation in select transplant subpopulations. Although smoking cessation increases adiponectin [34], this effect may depend on weight change and there were too few SA smokers in our cohort to examine its effect. Our study was limited by sample size in determining the relationship of adiponectin and prior MACE burden.…”
Section: Discussionmentioning
confidence: 99%